Pacific Equatorial Undercurrent: Mean state, sources, and future changes across models - Stellema, Annette; Sen Gupta, Alex; Taschetto, Andréa S.; Feng, Ming (Frontiers in Climate, 2022)
The Equatorial Undercurrent (EUC) stretches across the Pacific, transporting cool waters rich in oxygen and nutrients eastward to one of the most productive regions in the ocean. As an intricate part of the global climate system, EUC dynamics are essential to understanding future climate change but are poorly represented in global coupled climate models. This study examines EUC representation and future changes in the latest generations of the Coupled Model Intercomparison Project (CMIP6 and CMIP5) and an eddy-permitting ocean model. We also examine historical and projected changes in EUC source waters, including the Mindanao Current (MC), New Guinea Coastal Undercurrent (NGCU), and interior thermocline convergence. The circulation features in the models are broadly consistent with observations and ocean reanalyses, but improvements from CMIP5 to CMIP6 are limited. In the future projections, the EUC is enhanced in the western Pacific, with less prominent changes in CMIP6, but more so in the eddy-permitting model. The western Pacific EUC enhancement is likely associated with a wind-driven redirection of waters south of the equator, in which the NGCU boundary flow increases while the interior thermocline convergence decreases. This is superimposed on an overall weakening of the North Pacific subtropical overturning cell, including the MC, interior thermocline convergence, and Ekman divergence. As EUC heat and nutrient composition is linked to its sources, these projected changes have implications for the EUC's role in air–sea feedbacks, nutrient replenishment, and oxygen minimum zone ventilation in the eastern Pacific.